Internalization of Clostridium botulinum C2 Toxin Is Regulated by Cathepsin B Released from Lysosomes - Masahiro Nagahama; Keiko Kobayashi; Sadayuki Ochi; Masaya Takehara (Toxins, 2021)
Clostridium botulinum C2 toxin is a clostridial binary toxin consisting of actin ADP-ribosyltransferase (C2I) and C2II binding components. Activated C2II (C2IIa) binds to cellular receptors and forms oligomer in membrane rafts. C2IIa oligomer assembles with C2I and contributes to the transport of C2I into the cytoplasm of host cells. C2IIa induces Ca2+-induced lysosomal exocytosis, extracellular release of the acid sphingomyelinase (ASMase), and membrane invagination and endocytosis through generating ceramides in the membrane by ASMase. Here, we reveal that C2 toxin requires the lysosomal enzyme cathepsin B (CTSB) during endocytosis. Lysosomes are a rich source of proteases, containing cysteine protease CTSB and cathepsin L (CTSL), and aspartyl protease cathepsin D (CTSD). Cysteine protease inhibitor E64 blocked C2 toxin-induced cell rounding, but aspartyl protease inhibitor pepstatin-A did not. E64 inhibited the C2IIa-promoted extracellular ASMase activity, indicating that the protease contributes to the activation of ASMase. C2IIa induced the extracellular release of CTSB and CTSL, but not CTSD. CTSB knockdown by siRNA suppressed C2 toxin-caused cytotoxicity, but not siCTSL. These findings demonstrate that CTSB is important for effective cellular entry of C2 toxin into cells through increasing ASMase activity.